Dinoflagelados (Dinophyceae) de la laguna de Tamiahua, Veracruz, México - Figueroa-Torres, Ma. Guadalupe; Weiss-Martínez, Isaac (Revista de Biología Tropical, 1999)
In this paper we present the taxonomic composition of the dinoflagellates in the coastal lagoon of Tamiahua. Their role as toxic organisms and as cause of red tides is also analized. The material studied was collected during May and November 1996, and March, May and October 1997. The samples were taken using van Dorn bottles and a standard net (54 µm mesh). 35 taxa were registered, of which 23 are new records for the surveyed area. 24 species have been reported as agents causing red tides and seven correspond to toxic species. Among the most conspicuons species identified are:: Ceratium furca var. Hircus, Gymnodinium sp. 1, Scrippsella trochoidea, Prorocentrum micans, Dinophysis caudata, Gymnodinium sp. 2, Gyrodinium spirale, Oxyphysis oxitaxoides, Protoperodium conicum y Noctiluca scintillans.